2015
DOI: 10.1007/s12053-015-9364-0
|View full text |Cite
|
Sign up to set email alerts
|

How moving home influences appliance ownership: a Passivhaus case study

Abstract: Low carbon dwellings shift the focus to electricity consumption and appliances by significantly lowering space heating energy consumption. Using a UK Passivhaus (low carbon) case study, interviews and pre/ post-move-in appliance audits were employed to investigate how moving home can change the appliance requirements of appliance-using practices. Changes in appliance ownership were due to differences in how appliance-using practices (e.g. cooking, laundering, homemaking) were being performed. Existing/new appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…Outcomes from this suggest occupants to have relatively less impact on building performance in very low energy design than other types (though this may also be due to better user understanding of the principles of operation). Results of recent research involving a new Passive House development showed that occupants might also alter their use and ownership of household appliances and therefore affect associated electrical energy consumption as a result of moving to low energy homes [40].…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Outcomes from this suggest occupants to have relatively less impact on building performance in very low energy design than other types (though this may also be due to better user understanding of the principles of operation). Results of recent research involving a new Passive House development showed that occupants might also alter their use and ownership of household appliances and therefore affect associated electrical energy consumption as a result of moving to low energy homes [40].…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…These practices, consciously or not, drive the ‘practical rational’ behind appliance purchase decisions of individuals and households (Røpke, 2009). Practice-related research demand examinations of broader social processes that place the onus on the practices and how they are performed by households, instead of individuals as energy consumers or appliance users (Foulds et al, 2016). Social practise theory (SPT) is a tool to study such social processes.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the change in practices by using an appliance motivates occupants to purchase solar energy appliances. Foulds et al (2016), investigated the trend in appliance purchasing amongst occupants who changed home to energy-efficient houses in the UK have found that moving home can change the appliance requirements. The social-meaning of specific appliance-using practices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the application of social practice theory from 2015 to date has been largely in the context of household energy use and demand; more specifically related to electricity consumption and usage [108][109][110][111][112][113][114][115][116][117][118][119] and thermal comfort [120][121][122][123][124][125][126][127][128][129].…”
Section: Discussionmentioning
confidence: 99%